San Fernando Hill from Pointe-a-Pierre Trinidad - (:unkn) unknown (My University, 2010)
This postcard features the San Fernando or Naparima Hill circa the 1920s (dome-shaped with a flattened top on the horizon) located in San Fernando which is south of Pointe-a-Pierre, seen in the middle and foreground here with much of its land under cultivation. There is a road which bends around the fields near the sea shore and T-shaped electricity poles outline the road's edge. The body of water on the far right, next to large oil storage tanks and coconut trees, is the Gulf of Paria. On the ground between the ponds at right are a series of thin pipe lines. In 1912, the Pointe-a-Pierre area consisted of the thriving sugar estates of Plaisance, Bon Accord, Bonne Aventure, Plein Palais, La Carriere and Concorde. In 1913, the estates were bought by an oil company called Trinidad Leaseholds Limited and used to establish an oil refinery and oil storage deposit.
Colour: Sepia; Style: Landscape; Other: Bordered; Undivided
Keywords: Trinidad and Tobago; Postcards; [1926]; Sugarcane--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--San Fernando; Mountains--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Pointe-a-Pierre; Hills (San Fernando, Trinidad and Tobago)